An Investigation Into the Thesis/Dissertation Writing Experiences of Mandarin-Speaking Masters Students in New Zealand - Chang, Evelyn Chiungying (Auckland University of Technology, 2007)
This study explores the perceptions of Mandarin-speaking Masters students involved in the thesis/dissertation writing process. As Mandarin-speaking students form a sizeable part of the EAL [English as Additional Language] postgraduate cohort in New Zealand, it is important to explore their experiences. The aim of the proposed study is to provide an opportunity for these learners to express issues that are pertinent to them in this area. The study recruited 37 Masters Students from five universities to participate in the survey; 6 of these participants volunteered to be interviewed. Two aspects of the participants' perceptions were examined: the acquisition of academic literacy in English and the role of the supervisor in relation to their thesis writing. Findings indicated that students had underestimated how difficult it would be to study at this level in a foreign language and in a new sociocultural environment. They also indicated that the language assistance provided by supervisors was perceived to be very helpful and that mutual understanding and personal interaction between supervisors and students is crucial for successful supervision. However, better structured academic and pastoral support is required from the host universities. In addition, participants placed great emphasis on their personal growth and learning. The significance of the study lies in its cross-cultural accounts of the underlying complexities involved in EAL thesis writing. Findings underline the need for New Zealand universities to recognise the importance of cross-cultural awareness and its role in fostering campuses that are interculturally friendly.